GROWTH PERFORMANCE, CARCASS CHARACTERISTICS AND COST BENEFITS OF BROILER CHICKENS FED DIETARY LEVELS OF RICE OFFAL AS SUBSTITUTE FOR WHEAT OFFAL - Haruna, I. M.; Bello, K. M.; Doma, U. D.; Egbo, M. L.; Jamaa, N.A.; Ambore, C.B.; Apeh, D.; Gukut, M. Y.; Rukayya, Y. L. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study evaluated the growth performance, carcass characteristics, and cost-effectiveness of replacing wheat offal with rice offal in broiler chicken diets. A total of 300 unsexed broiler chicks were randomly assigned to four dietary treatments containing 0%, 33.33%, 66.67% and 100% level of rice offal as substitute for wheat offal coded as Diet 1, 2, 3 and 4 respectively. The experimental design was a completely randomized design with 75 birds per treatment (18 birds per replicate) and the feeding trial lasted for 56 days. Feed and water were supplied ad libitum. Results showed no significant differences in growth performance parameters across treatments. However, plucked weight was significantly affected (P < 0.05), with the highest value observed on diet 1. Dressing percentage (71.31–76.18%) remained unaffected. Economic analysis revealed that feed cost decreased as rice offal inclusion increased, with the lowest feed cost per kg weight gain (₦944.43) and highest cost savings (₦58.32) recorded on diet 3 (66.67% rice offal). The study concludes that rice offal can fully replace wheat offal without adverse effects on broiler performance, with 66.67% inclusion being the most economic diet and is recommended for broiler chicken production in the study area.